Severe panuveitis – uncommon presentation of cat scratch disease - Che Mohd Hazidi, Sahel Akmal; Rosli, Abdul Hadi; Jabbari, Aidila Jesmin (Wolters Kluwer Health, 2026)
Cat scratch disease (CSD) is a systemic infectious illness caused by the Bartonella henselae and usually transmitted to humans directly through bites, scratches, or licks. The most common posterior segment ocular complication of B. henselae is neuroretinitis. Also reported in the literature are a few unusual retinal presentations including retinal white spots, retinal vasoproliferative lesions, papillitis, macular hole, vitreal detachment, vitritis, and branch retinal artery and venous occlusions. This case report describes a CSD patient who presented with unilateral severe panuveitis. This case highlights another posterior segment presentation of CSD. A 7‑year‑old boy presented with reduced vision in the right eye for 3 days following cat scratch over the right conjunctiva and lower lid 1 week before. Visual acuity in the right eye was counting finger and the left eye was 6/6. There was no relative afferent papillary defect. The right conjunctiva was mildly injected with healed scar. The intraocular pressure was normal. There was the presence of grade four anterior chamber cells but no hypopyon seen. The right posterior segment showed the presence of vitritis, hyperaemic optic disc swelling, vasculitis, and retinitis lesion. He underwent intravitreal tapping and vancomycin and ceftazidime injection. Subsequently, trans pars plana vitrectomy was performed due to worsening ocular condition and visual acuity (hand movement). The serology investigation was positive for B. henselae. The patient was treated with systemic and topical antibiotics up to 6 weeks. Systemic steroid was added subsequently after the infection was controlled. Following treatment, the ocular inflammations had resolved. The final visual acuity of the right eye was 6/6. Published articles on severe panuveitis as presentation of CSD are extremely limited. A high index of suspicion will facilitate the diagnosis and management, especially in the patient with a history of cat scratch.